A "turn-on" ESIPT fluorescence probe of 2-(aminocarbonyl)phenylboronic acid for the selective detection of Cu(ii). Issue 48 (31st October 2022) - Jiang, Dandan; Zheng, Minghao; Yan, Xiaoyang; Huang, Bin; Huang, Hui; Gong, Tianhao; Liu, Kunming; Liu, Jinbiao
Abstract : Herein, we report a highly selective fluorescent probe for the detection of Cu(ii ). Abstract : Herein, we report a highly selective fluorescent probe for the detection of Cu(ii ). The detection mechanism relies on the Cu(ii )-catalyzed oxidative hydroxylation of 2-(aminocarbonyl)phenylboronic acid into salicylamide, thus recovering the excited-state intramolecular proton transfer (ESIPT) effect and inducing more than 35-fold fluorescence enhancement. The simple structure and readily available fluorescent probe give a novel method for quantitatively detecting Cu(ii ) in the linear range of 0–22 μM, with a limit of detection down to 68 nM, and exhibiting high selectivity for Cu(ii ) over 16 other metal ions.